Management Earnings Guidance and Stock Price Crash Risk - HAMM, Sophia J. W. (Institutional Knowledge at Singapore Management University, 2012)
Hutton, Marcus, and Tehranian (JFE 2009) show that more transparent financial reporting of earnings reduces the likelihood of a future stock price crash. We extend their work by examining how management earnings guidance is related to such crash risk. Accounting for endogeneity in guidance decisions, we find that higher annual guidance frequency is associated with higher crash risk, which contrasts with the notion that more guidance enhances transparency and reduces crash risk. Consistent with agency problems being an explanation, we find that the positive association is stronger for firms with higher executive stock ownership, weaker external monitoring, lower litigation risk, more upward-biased forecasts, and more opaque earnings. We also show that the association is weaker after the Sarbanes-Oxley Act, consistent with the act curbing agency problems. A key implication of our findings is that more guidance does not necessarily lead to better capital market outcomes.